May & Company, Hardware; John W. Lord, Sheet Iron & Tin Ware; S. & J. Myers, Watches; inside back cover - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of May & Company, Hardware; John W. Lord, Sheet Iron & Tin Ware; S. & J. Myers, Watches; inside back cover from the 1870 Boston City Directory